Corilagin Ameliorates Atherosclerosis in Peripheral Artery Disease via the Toll-Like Receptor-4 Signaling Pathway in vitro and in vivo - Li, Yiqing; Wang, Yujie; Chen, Yunfei; Wang, Yao; Zhang, Shaojun; Liu, Pan; Chen, Zhilin; Song, Peng; Luo, Lei; Luo, Yingying; Dang, Yiping; Zhao, Lei (Frontiers in Immunology, 2020)
This study tried to explore whether corilagin would ameliorate or reverse the atherosclerotic development via toll-like receptor 4 (TLR4) signaling pathway in vitro and in vivo. Ana-1 cells or Mouse Peritoneal Macrophages (MPMs) were stimulated with ox-LDL followed by corilagin treating in gradient of concentration. TLR4 expression in Ana-1 cells was up-regulated by lentiviral transduction and down-regulated by siRNA. Peripheral blood mononuclear cells (PBMCs), plasma samples and femoral arteries were collected from rat peripheral artery disease (PAD) models. Both mRNA and protein expression of TLR4 and downstream molecules were significant decreased by corilagin in Ana-1 cells, MPMs and PBMCs from animal models, and the reduction was still existing either down- or up-regulate TLR4 in Ana-1 cells. Corilagin also exerted a prominent effect on the changes in plasma cytokines and the pathological manifestation of atherosclerosis in femoral arteries. Corilagin could ameliorate the development of atherosclerotic plaque via inhibiting TLR4 signal pathway in monocyte/macrophage and reducing the release of inflammatory cytokines. This study provided a new therapeutic target and the new nichetargeting drug to oppose atherosclerosis and showed the enormous potential of Corilagin to control PAD in human.